Analisis Lambannya Adopsi Rencana Aksi Nasional Resolusi Dewan Keamanan PBB 1325 sebagai Implementasi Women, Peace and Security (WPS) Agenda di Myanmar - Putri Rahma Asri (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2023)
Gender in conflict is obscured in the mainstream of conflict analysis to date. The complexity of conflict is simplified by focusing on men as the sole actor and leaves the experiences and perspectives of women behind. This dynamic has been happening in Myanmar during the civil war and under the military regime which causes insecurity among Myanmar women. Unfortunately, Myanmar has not successfully translated UN Security Council Resolution (UNSCR) 1325 into National Action Plan (NAP) as a policy that ensures the safety of women in conflict situations. Their adoption process has been only at the initial stage. Meanwhile, Myanmar still refers to National Strategic Plan for the Advancement of Women (NSPAW) which is irrelevant to the Women, Peace and Security (WPS) agenda implementation. Therefore, this qualitative-explanatory research aims to understand the reasons for the slow adoption of NAP on UNSCR 1325 in Myanmar using the gender regime concept from Feminist Institutionalism and the positionality concept from Feminist Security Studies. Based on the analysis, there are two factors causing the slow adoption. First, Myanmar institution from 2011 to 2022 is not friendly to gender issues and there is a regression in Myanmar institution from feminist presence and masculinist backlash regime to masculine hegemony regime that produces gender-blind policies. Second, Myanmar government’s positionality on security is contrary to the norms contained in Resolution 1325. They reflect on NSPAW 2013-2022 implementation which encourages them to ensure their compliance with regard to women in conflict situations.